Drying of fish in Khar Danda Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
In Khar Danda Koliwada, it is common to see fish drying on lines, swaying gently in the breeze. The fish are strung together with twine and hung from hooks or lines.